Differences in Learning Characteristics Between Students With High, Average, and Low Levels of Academic Procrastination: Students’ Views on Factors Influencing Their Learning - Visser, Lennart; Korthagen, Fred A. J.; Schoonenboom, Judith (Frontiers in Psychology, 2018)
Within the field of procrastination, much research has been conducted on factors that have an influence on academic procrastination. Less is known about how such factors may differ for various students. In addition, not much is known about differences in the process of how factors influence students’ learning and what creates differences in procrastination behavior between students with different levels of academic procrastination. In this study learning characteristics and the self-regulation behavior of three groups of students with different levels of academic procrastination were compared. The rationale behind this was that certain learning characteristics and self-regulation behaviors may play out differently in students with different levels of academic procrastination. Participants were first-year students (N = 22) with different levels of academic procrastination enrolled in an elementary teacher education program. The selection of the participants into three groups of students (low procrastination, n = 8; average procrastination, n = 8; high procrastination, n = 6) was based on their scores on a questionnaire measuring the students’ levels of academic procrastination. From semi-structured interviews, six themes emerged that describe how students in the three groups deal with factors that influence the students’ learning: degree program choice, getting started with study activities, engagement in study activities, ways of reacting to failure, view of oneself, and study results. This study shows the importance of looking at differences in how students deal with certain factors possibly negatively influencing their learning. Within the group of students with average and high levels of academic procrastination, factors influencing their learning are regularly present. These factors lead to procrastination behavior among students with high levels of academic procrastination, but this seems not the case among students with an average level of academic procrastination.